A review of the pleasing lacewing genus Dilar Rambur (Neuroptera, Dilaridae) from Southeast Asia - Zhang, Wei; Liu, Xingyue; Winterton, Shaun L.; Aspöck, Horst; Aspöck, Ulrike (Zootaxa, 2016)
The lacewing family Dilaridae (pleasing lacewings) is poorly known in Southeast Asia, currently with only five described species. In this paper, we provide a revision of the species of the genus Dilar Rambur, 1838 from Southeast Asia. Eleven species of Dilar are recorded in this region, with seven species herein described as new to science, i.e. Dilar abnormis Zhang, Liu & Winterton, sp. nov., Dilar lineatus Zhang, Liu & Winterton, sp. nov., Dilar loeinensis Zhang, Liu, Winterton, sp. nov., Dilar ohli Zhang, Liu, Aspöck & Aspöck, sp. nov., Dilar rotundatus Zhang, Liu & Winterton, sp. nov., Dilar sumatranus Zhang, Liu, Aspöck & Aspöck, sp. nov., and Dilar zimmermannae Zhang, Liu, Aspöck & Aspöck, sp. nov. Re-descriptions of Dilar grandis (Banks, 1931), and Dilar marmoratus (Banks, 1931) are also provided. Dilaridae are recorded in Indonesia (Sumatra), Myanmar, and northern Thailand for the first time. A key to the Dilar species from Southeast Asia is given.